A new species of Macrolobium (Fabaceae, Detarioideae) endemic on a Tepui of the Guyana Shield in Brazil - Farroñay, Francisco; Adrianzén, Marisabel U.; Perdiz, Ricardo De Oliveira; Vicentini, Alberto (Phytotaxa, 2018)
Macrolobium aracaense (Fabaceae), a new endemic treelet species from Brazil, is here described and illustrated. Morphologically it is similar to M. longipes: both are treelets, the leaflets have the same shape and are covered by papillary epidermis on the abaxial surface, and the sepals apex are minutely ciliate. Macrolobium aracaense occurs in sympatry with M. discolor var. discolor and M. gracile var. confertum in Serra do Aracá State Park, Amazonas, Brazil, and these four species can be easily differentiated by morphological characters, and their similarities and differences are here discussed.